2015
DOI: 10.1007/s00508-015-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

Can platelet indices be used as predictors of complication in subjects with appendicitis?

Abstract: Our findings suggested these, MPV values in cases of appendicitis without complication were lower than the cases with complication and healthy control and MPV is a predictor of the development of complication in subjects with appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
2
25
0
3
Order By: Relevance
“…While there are many studies that have mainly focused on mean platelet volume (MPV), there are very few studies on other platelet indicators including PDW and PCT, especially in the pediatric age group. [2][3][4][5][6][7][8][9][10][11][12][13] PDW is an indicator of platelet volume variability in size, indicating morphological changes and platelet reactivity. The activation of platelets causes morphological changes that increase PDW.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are many studies that have mainly focused on mean platelet volume (MPV), there are very few studies on other platelet indicators including PDW and PCT, especially in the pediatric age group. [2][3][4][5][6][7][8][9][10][11][12][13] PDW is an indicator of platelet volume variability in size, indicating morphological changes and platelet reactivity. The activation of platelets causes morphological changes that increase PDW.…”
Section: Discussionmentioning
confidence: 99%
“…While some of these studies have demonstrated a correlation between PDW and AA, others have reported no change in the value of PDW. 2,[7][8][9][10][11][12][13][14] Many of these studies have been conducted on adults, and only one has studied children. Dinc at al first reported that PDW may be a supportive parameter in the diagnosis of AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical diagnosis of appendicitis is challenging, especially in younger children who cannot verbalize their symptoms and in whom the physical examination is often unreliable . Laboratory studies and clinical scores, like the Alvarado score and the Pediatric Appendicitis Score, do not confer significant sensitivity or specificity to dictate management when used alone …”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] AA'lı erişkinlerde OTH değişimiyle ilgili çalışmalar da giderek artmaktadır. [16][17][18][19][20][21][22] AA'lı çocuklarda OTH değişimini sorgulayan az sayıda çalışma vardır. [23][24][25] Bu çalışmada birincil olarak çocukluk yaş grubunda OTH'nin AA tanısındaki değerinin, ikincil olarak ise AA'da komplikasyon varlığının OTH değeri üzerine olan etkisinin araştırılması amaçlandı.…”
unclassified